Effect of the distance between adherent mesenchymal stem cell and the focus of irradiation of femtosecond laser on cell replication capacity - Sakai, Jun (Springer Netherlands, 2012)
The effect of femtosecond laser irradiation on adherent mesenchymal stem cell was investigated with the aim to develop a novel noninvasive cell purification system. A single mesenchymal stem cell was irradiated with a femtosecond laser on the center of the cell using several energy values and the cell lost its replication capacity with one time irradiation with an energy of 2.0 μJ. Besides at a neighbor point in the major axis, when irradiated in the minor axis at a distance shorter than 10 μm, the cell stopped its replication capacity. The accumulation effect of cell damage caused by multiple laser shots at a neighbor point in the minor axis was correlated with the critical distance at which the cell lost its replication capacity. Finally, a novel equation of laser cell damage as a function of laser pulse energy and laser shot number is proposed.